المشكلات المهنية المرتبطة بثقافة المجتمع - ترزولت عمروني, حورية; لعيجلات, يوسف (جامعة الوادي University of Eloued, 2018)
هدفت الدراسة إلى التعرف على أهمية المشكلات المهنية لمدرسي التربية البدنية والرياضية في المدرسة الجزائرية المرتبطة بثقافة المجتمع والتعرف على درجة حدتها. ولتحقيق أهداف الدراسة قام الباحثان بإعداد استمارة استبيان تضمنت قائمة من المشكلات المهنية لاستخدامها كأداة للقياس، بعد التأكد من صدق الأداة وثباتها تم التوصل إلى الصورة النهائية للأداة والتي أصبحت تضم 18 فقرة، تم تطبيق الأداة بعد ذلك على عينة بلغت 116 مدرس من الطورين الإعدادي والثانوي. وقد توصلت الدراسة إلى أن المشكلات المهنية المرتبطة بثقافة المجتمع لدى مدرسي التربية البدنية والرياضية في المدرسة الجزائرية هي مشكلات لها أهمية كبيرة، كما اتضح أن المشكلات المهنية المرتبطة بثقافة المجتمع لدى مدرسي التربية البدنية والرياضية في المدرسة الجزائرية بدرجة حدة مرتفعة هي على الترتيب حسب درجة حدتها هي مؤسسات المجتمع، ونظرة الأولياء، اما المشكلات المهنية المرتبطة بعلاقات المدرس جاءت بدرجة حدة متوسطة. ويوصي الباحثان بضرورة ترشيد النفقات والجهد والوقت نحو ممارسات مهنية تخضع للشروط العلمية بما يسهل مهام مدرسي التربية البدنية والرياضية من أجل تحقيق الأهداف التربوية والرياضية التي يتطلع اليها المجتمع. The aim of this study was to identify the importance of Vocational problems of teachers of physical education and sports in Algerian schools related to the community culture and to identify the degree of severity. To achieve the objectives of the study the researchers prepared a questionnaire included a list of Vocational problems related to the Community culture to be used as a tool for measuring, after making sure the veracity of the tool and its stability arrived to the final form of the tool, which has become a 18-paragraph, the tool was applied then on the sample of 116 teachers from the preparatory and secondary level. The study results show that the big importance of Vocational problems related to the Community culture at teachers of physical education and sports in Algerian schools, as it turned out that has degree Severity high, and those respectively by degree of Severity as follows: society institutions, parents look, But the Vocational problems concerning relations teacher are the problems of her medium Severity degree. The researchers recommend to rationalization of expenditure and effort and time towards the professional practices subject to scientific conditions order to facilitate teacher tasks of physical education and sports in order to achieve national goals of education and sports, That the community looking forward to it.
لدى مدرسي التربية البدنية والرياضية
مقال
Keywords: المدرس؛ الرياضة؛ التربية البدنية؛ المشكلات المهنية؛ ثقافة المجتمع; teacher, sports; physical education; vocational problems; community cultur